Chasing Aphrodite : the hunt for looted antiquities at the world's richest museum - Felch, Jason, (Houghton Mifflin Harcourt, 2011)
Drawing on a trove of confidential museum records and frank interviews, Felch and Frammolino give a fly-on-the-wall account of the inner workings of a world-class museum and tell the story of the Getty's dealings in the illegal antiquities trade. Fast-paced and compelling, "Chasing Aphrodite" exposes the layer of dirt beneath the polished facade of the museum business.